RESULTS OF TROLLING LINE OPERATIONS IN GOA WATERS DURING 1965-68 - Dhawan, Rajinder M; Namboothiri, P V S; Gopinathan, V G (Indian Journal of Fisheries, 2011)
The results of trolling line operations conducted for the first time in Goa waters bythe Directorate of Fisheries, Panaji, during the years 1965-68 have been discussed. Theseoperations, in later years, led to starting of a small commercial fishery. The trollingline catches are constituted by Scomberomorus commerson, Chorinemus lysan, Caranxsansun, Sphyraena sp.. Chirocentrus dorab, Rachycentron canadus, Euthytmus affinis andThynnus mapropterus. The size groups, gonadal condition and food of Scomberomoruscommerson and Chorinemus lysan which were the two main species in the fishery have bsendescribed.